The impact of chemotherapy on survival of patients with extremity and trunk wall soft tissue sarcoma: revisiting the results of the EORTC-STBSG 62931 randomised trial. (March 2019) - Pasquali, Sandro; Pizzamiglio, Sara; Touati, Nathan; Litiere, Saskia; Marreaud, Sandrine; Kasper, Bernd; Gelderblom, Hans; Stacchiotti, Silvia; Judson, Ian; Dei Tos, Angelo P.; Verderio, Paolo; Casali, Paolo G.; et al.
Abstract: Background: This study was aimed at determining whether patients with high-risk soft tissue sarcoma (STS), as identified using the nomogram Sarculator, benefitted from adjuvant chemotherapy in the EORTC-STBSG 62931 randomised controlled trial (RCT), which failed to detect an impact for adjuvant doxorubicin plus ifosfamide (Adj) over observation (Obs). Methods: Patients with extremity and trunk wall STS in the EORTC-STBSG 62931 RCT were analysed (N = 290/351). Ten-year predicted probability of overall survival (pr-OS) was calculated using the prognostic nomogram Sarculator. Patients were grouped into three categories of predicted pr-OS: high (pr-OS>66%), intermediate (51<pr-OS≤66) and low (pr-OS≤51%). OS and disease-free survival (DFS) were calculated. Results: Nomogram pr-OS was dispersed (median 72%, interquartile range 57–83%) and had prognostic value for OS and DFS (log-rank test: P < 0.001). One hundred seventy, 68 and 52 patients had high (58.6%, 90 Obs/80 Adj), intermediate (23.5%, 34 Obs/34 Adj) and low pr-OS (17.9%, 24 Obs/28 Adj), respectively. Adjuvant chemotherapy halved the risk of recurrence (hazard ratio [HR] = 0.46, 95% confidence interval [CI] 0.24–0.89) and death (HR = 0.46, 95% CI 0.23–0.94) in the low pr-OS category, while no effect was detected in intermediate and high pr-OS categories. To strengthen these findings, study participants with pr-OS<60% were combined (N = 80, 27.6%, 39 Obs/41 Adj), and a significant DFS (HR = 0.49, 95% CI 0.28–0.85) and OS (HR = 0.50, 95% CI 0.30–0.90) benefit was detected. Conclusion: Patients of the EORTC-STBSG 62931 RCT with extremity and trunk wall STS and a low predicted pr-OS (high-risk patients) had better outcomes when treated with adjuvant chemotherapy. This may help reconcile the disparate results of clinical studies on adjuvant/neoadjuvant chemotherapy in STS. Highlights: The EORTC 62931 failed to detect an OS benefit for adjuvant chemotherapy in soft tissue sarcoma (STS). The prognostic tool Sarculator was used to stratify prognosis of enrolled patients. Sixty percent of patients were at low risk and did not benefit from adjuvant chemotherapy. Adjuvant chemotherapy halved the risk of death in high-risk participants. This analysis explains conflicting results on adjuvant chemotherapy for STS.